Barriers and accessibility in public squares: evidence from small towns in Upper Silesia (Poland) - Kleszcz, Justyna; Szczegielniak, Anna; Gałkowski, Marcin; Brożyna, Weronika; Adamska, Monika Ewa; Mordak, Arkadiusz; Kulińska, Ewa; Masłowski, Dariusz (Bulletin of Geography. Socio-economic Series, 2026)
Citizens have a fundamental right to access public spaces. Since the adoption of the UN Convention on the Rights of Persons with Disabilities in 2008, significant changes have been made to Polish law. This study aims to assess the accessibility of public spaces in Poland, using case studies of public squares in small towns. The research focuses on the region of Opole Silesia. Six towns were selected for the analysis. The research followed a two-stage approach – a structured literature review and field research, followed by an analysis of numerical and spatial data collected through a participatory access assessment method. The findings show that none of the spaces provide safe and independent mobility conditions for individuals with physical disabilities or blind or partially sighted persons. ...